2022
DOI: 10.3389/fpubh.2022.981780
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of nursing practitioners' experiences with COVID-19 patients dying alone in Greece

Abstract: BackgroundIn Greece, there is still limited research on death in isolation due to COVID-19. This deserves attention because of the recent financial crisis, which profoundly impacted public health, and the high relevance of the Hippocratic tradition to the moral values of clinical practice.MethodsA prospective qualitative study using in-depth interviews with 15 frontline nursing practitioners working in a COVID-19 ward or intensive care unit (ICU) was conducted from July 2021 to December 2021.ResultsThe inabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…They provided care beyond limits, becoming, in some cases, the closest relative of the patient, supporting the patients who were dying alone and the families who were not able to say goodbye to their loved ones. Similar findings are reported in the relevant literature, as the absence of the family created new patterns in nurse-patient communication and developed strong bonding relationships between caregivers and patients [ 28 - 30 ]. Jia et al demonstrated that family visitation restrictions directed nurses towards offering a wide range of support to their isolated patients and adopting a mediating role between the patients and their families [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They provided care beyond limits, becoming, in some cases, the closest relative of the patient, supporting the patients who were dying alone and the families who were not able to say goodbye to their loved ones. Similar findings are reported in the relevant literature, as the absence of the family created new patterns in nurse-patient communication and developed strong bonding relationships between caregivers and patients [ 28 - 30 ]. Jia et al demonstrated that family visitation restrictions directed nurses towards offering a wide range of support to their isolated patients and adopting a mediating role between the patients and their families [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Deep and intense feelings of sadness and distress were experienced by the nurses as they were confronted with the patient, who was dying alone. This issue was discussed in the relevant literature by underscoring the need for the family to be next to the dying patient and the need for the dying patient to be surrounded by his/her relatives [ 30 - 33 ]. In consistency with the findings of the present study, Feder et al's study highlights the importance of sharing feelings of loss and mourning in cases where relatives were unable to be next to their loved ones even after death [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deaths in solitude are caused by the rules of isolation of COVID‐19 to prevent the spread of the virus. Such situations may have serious and unknown psychological consequences for family members and healthcare providers, such as feelings of helplessness, hopelessness, guilt, moral distress and long‐term, complicated grief (Voultsos et al, 2022). In a study, it is stated that dying alone is an unprecedentedly unbearable and devastating experience and is not compatible with what is called a “good death” (Voultsos et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Such situations may have serious and unknown psychological consequences for family members and healthcare providers, such as feelings of helplessness, hopelessness, guilt, moral distress and long‐term, complicated grief (Voultsos et al, 2022). In a study, it is stated that dying alone is an unprecedentedly unbearable and devastating experience and is not compatible with what is called a “good death” (Voultsos et al, 2022). But due to public health restrictions, patients die alone (Chochinov et al, 2020), and in this study, participants have stated that their colleagues died alone, which affected their mourning process.…”
Section: Discussionmentioning
confidence: 99%